Novas Gimnospermas e possivel Angiosperma da Paleoflora Crato, Eocretaceo da Bacia do Araripe, Nordeste do Brasil - Fanton, Jean Carlo Mari, 1983- (2007)
Orientadores: Fresia Soledad Ricardi-Branco, Mary Elizabeth Cerruti Bernardes-de-Oliveira